Surgical Results of Triamcinolone Assisted Pars Plana Vitrectomy Combined with Phacoemulsification in Diabetic Patients - Birinci, Hakki (Bentham Science Publishers Ltd., 2008)
PURPOSE: It is aimed to evaluate the technical feasibility, safety, outcome, and incidence of complications after clear corneal phacoemulsification with foldable intraocular lens implantation (IOL) and triamcinolone assisted pars plana vitrectomy in patients with proliferative diabetic retinopathy. METHODS: The results of combined phacoemulsification, in the capsular bag foldable intraocular lens implantation and triamcinolone assisted pars plana vitrectomy in 75 eyes of 72 patients, were retrospectively evaluated. Surgery was performed using general anesthesia in 9 cases, and monitored retrobulbar block in 66 cases. In all cases, phacoemulsification with clear corneal incision and foldable acrylic IOL implantation were performed before vitreoretinal surgery. The main investigation points were preoperative and postoperative best corrected visual acuity (BCVA), and intraoperative and postoperative complications. RESULTS: The mean age at surgery was 62.07 ± 9.51 years (range 22 to 78 years) and the postoperative follow-up time was 17.17 ± 7.25 months. All eyes had clinically significant cataract that interfered with visualization of the retina preoperatively. All eyes had proliferative diabetic retinopathy. Postoperatively, visual acuity improved in 65 eyes (86.7%), was unchanged in 9 eyes (12.0%), and decreased in 1 eye (1.3%). The most postoperative complications consisted of a mild iritis in 8 eyes (10.7%), recurrent vitreous hemorrhage in 8 eyes (10.7%), posterior capsule opacification in 7 eyes (9.3%), transient intraocular pressure increase in 6 (8.0%), iatrogenic retinal tear in 6 (8.0%), epiretinal membrane in 5 (6.7%). CONCLUSION: The results of combined phacoemulsification in the capsular bag foldable IOL implantation and triamcinolone assisted pars plana vitrectomy show that visual acuity outcomes are generally favorable and complications are acceptable in diabetic patients. Visual results and complications depend primarily on the underlying posterior segment pathology. The use of triamcinolone acetonide may simplify surgery and decreases the postoperative inflammation.